Evaluation on Heat Transferring Performance of Fabric Heat Sink by Finite Element Modeling - 杨旭东 张华帅 胡吉永 路玉环 李毓陵 (东华大学学报（英文版）, 2016)
Considering the limitation in current manufacturing technology of commercial pin fin heat sinks, a new fabric heat sink has been designed. However, it is lack of an understanding of the heat transferring performance of this new kind of heat sink. In this study, the finite element method （FEM） was used to predict the heat transferring performance of fabric heat sink under the condition of natural convection and forced convection, and its heat transferring performance was compared with that of pin fin heat sink. The results showed that in the condition of natural convection the heat transferring performance of pin fin heat sink was better than that of fabric heat sink, and vice versa under the forced convection condition.